Placement and source effects of phosphate fertilizers on phosphorus availability and reaction products in two reduced-till soils: A greenhouse study - Khatiwada, Raju; Hettiarachchi, Ganga M.; Mengel, David B.; Fei, Mingwei (My University, 2015)
Crop yields are limited primarily by unavailability of nutrients in agricultural soil. Adoption of reduced tillage and no-tillage systems leads to stratification of nutrients in surface soil, so management of phosphorus (P) in these systems is a major issue. The objective of this research was to understand the influence of placement (broadcast vs. deep-placed P) and fertilizer source (granular versus liquid P) on the reaction products of P under greenhouse conditions using soil columns. Phosphorus was added at a rate of 75 kg/ha to two soils: an acid soil from Manhattan, KS, and a slightly acid to neutral soil from Ottawa, KS. At 5 weeks after P application soil pH, resin-extractable P, and speciation of P in soils were determined at different distances from the point of fertilizer application. Scanning electron microscope with energy dispersive X-ray analysis(SEM-EDXA) and synchrotron-based X-ray absorption near-edge structure (XANES) spectroscopy were used to understand P speciation. Results for P fertilizer sources and placement with respect to resin-extractable P showed no clear differences between the treatments except for granular broadcast and granular deep-placed treatments in the Ottawa soil.Reaction products formed after application of P in two soils showed some clear differences. The XANES speciation revealed that Fe-P-like forms dominated in the acidic soil, whereas adsorbed and Fe and Ca-P-like forms dominated in the neutral to slightly acid soil. No clear trends in reaction products were detected with respect to P source or the P placement method. Furthermore, SEM-EDXA analysis of incubated fertilizer granules extracted from soils at 5 weeks showed enrichment of Al, Fe, and Ca in the zones of remaining P in incubated granules, indirectly indicating that these cations enter and or remaining in the granules and begin to react with P before the granules dissolve completely.
Citation: Khatiwada, Raju, et al. “Placement and Source Effects of Phosphate Fertilizers on Phosphorus Availability and Reaction Products in Two Reduced-Till Soils: A Greenhouse Study.” Soil Science, vol. 179, no. 3, Mar. 2014, pp. 141–152. journals.lww.com, doi:10.1097/SS.0000000000000055.
Keywords: Phosphorus; Phosphorus speciation; Reduced tillage; Phosphorus placement; X-ray absorption near edge structure spectroscopy